Glycerin as alternative energy source in finishing beef cattle diets - Benedeti, Pedro Del Bianco (2016)
The present work was developed based on three studies. The objective of the firs study was to evaluate the effects of partially replacing dry ground corn with glycerin on ruminal fermentation using a dual-flow continuous culture system. Six fermenters (1,223 i 21 ml) were used in a replicated 3x3 Latin square arrangement with three periods of 10 d each, with 7 d for diet adaptation and 3 d for sample collections. All diets contained 75% concentrate and three dietary glycerin levels (0, 15, and 30% on dry matter basis), totaling six replicates per treatment. Glycerin levels did not affect apparent digestibility of DM (PLin. = 0.13; PQuad, 0.40), OM (Pm, = 0.72; PQuad, = 0.15), NDF (PLin. = 0.38; PQuad. = 0.50) and ADF (PLin- 0.91; PQuad. = 0.18). Also, glycerin inclusion did not affect true digestibility of DM (PLin. 0.35; PQuad_ = 0.48), and OM (Pm. = 0.08; PQuad_ = 0.19). Concentrations of propionate (P 0.01) and total volatile fatty acids (P < 0.01) increased linearly and concentrations of acetate (P < 0.01), butyrate (P = 0.01), iso-valerate (P < 0.01), and total branched-chain volatile fatty acids, as well as the acetate: propionate ratio (P < 0.01) decreased with glycerin inclusion. Linear increases on NH3-N concentration in digesta effluent (P < 0.01) and on NH3-N flow (P < 0.01) were observed due to glycerin inclusion in the diets. Crude protein digestibility (P 0.04) and microbial N flow (P = 0.04) were greater in the control treatment compared with the other treatments and responded quadratically with glycerin inclusion. Furthermore, the inclusion of glycerin linearly decreased (P = 0.02) non- ammonia N flow. Glycerin levels did not affect the flows of total N (PLin. = 0.79; PQuad. = 0.35), and dietary N (PLin, = 0.99; PQuad 0.07), as well as microbial efficiency (Put, = 0.09; PQuad. = 0.07). These results suggest that partially replacing dry ground corn with glycerin may change ruminal fermentation, by increasing total volatile fatty acids, and propionate concentration without affecting microbial efficiency, which may improve glucogenic potential of beef cattle diets. The second study was developed aiming to evaluate the effects of replacing dry ground corn with crude glycerin on intake, apparent digestibility, performance, and carcass characteristics of finishing beef bulls. A completely randomized block design experiment with 25 d for adaptation and 100 d for data collection was conducted, in which 3,640 Nellore bulls (367 ± 36.8 kg; 18 ± 3 mo) were blocked by body weight and assigned to 20 pens. Bulls were randomly assigned to one of four treatments: 0, 5, 10, and 15% (dry matter basis) of crude glycerin in the diet. Intake of dry matter, organic matter, and neutral detergent fiber decreased linearly (P < 0.05) with crude glycerin inclusion. However, crude glycerin levels did not affect (P > 0.05) intakes of crude protein, non-fiber carbohydrates, and total digestible nutrients. Digestibility of dry matter, organic matter, neutral detergent fiber, and total digestible nutrients increased quadratically (P < 0.05) with the inclusion of crude glycerin in the diet. Crude glycerin inclusion did not change the intake of digestible dry matter, average daily gain, final body weight, carcass gain, carcass dressing, gain-to-feed ratio, Longissimus thoracis muscle area, and back and rump fat thicknesses (P > 0.05). These results suggest that crude glycerin may be included in finishing beef diets at levels up to 15% without impairing performance and carcass characteristics. For the third study, five in vitro experiments were conducted to evaluate the metabolizable energy and changes on ruminal fermentation, total gas production and greenhouse gases concentration of glycerin compared to corn and starch, as well as when glycerin was added in finishing beef diets. For Exp. 1, a 24 bottles system (AnkomRF Gas Production System, Ankom technology, NY, USA) was used in 4 consecutive runs of 48 h. The treatments were three different feedstuffs: corn, glycerin, and starch. The 24 h total gas production, acetate concentration, and acetate: propionate ratio decreased (P < 0.01) only with feeding glycerin. The 48 h total gas production was highest (P < 0.01) for corn, and similar between glycerin and starch. The starch treatment presented the lowest (P = 0.01) total VFA concentration. Corn presented the lowest propionate concentration (P < 0.01). The metabolizable energy was highest (P < 0.01) for corn, and similar between glycerin and starch. For Exp. 2, the same system of Exp. 1 was used in 4 consecutive runs of 48h. The treatments were: inclusion of 0, 100, 200, and 30og/kg DM of glycerin replacing corn in finishing beef diets. Glycerin levels did not affect (P > 0.05) 24 h and 48 h total gas production, final pH, NHg-N, total VFA, propionate, and butyrate concentrations. The inclusion of glycerin linearly decreased acetate concentration (P 0.03) and acetate: propionate ratio (P = 0.04). For Exp. 3, a total of 20-serum bottles (155 mL) were used in 4 consecutive runs of 48h. The treatments were the same of Exp. 1. The CH4 concentration increased (P < 0.01) only with feeding glycerin. The Co2 in ml/g was higher (P < 0.01) for corn, but similar for glycerin and starch. The pH decreased (P < 0.01) only with feeding starch. Different feedstuffs had no effect (P > 0.05) on total VFA, and propionate concentration. Compared with glycerin treatment, acetate concentration (P 0.01) and acetate: propionate ratio (P = 0.01) were higher for corn and starch, whereas butyrate and valerate concentrations were higher (P = 0.01) for glycerin. For Exp. 4, a total of 25-serum bottles (155 mL) were used in 4 consecutive runs of 48h. The treatments were the same of Exp. 2. The glycerin inclusion did not affect (P > 0.05) the concentrations of CH4, Co2, final pH, and total VFA, propionate, butyrate, and acetate: propionate ratio. A linear decrease of acetate concentration (P = 0.04) was observed due to inclusion of glycerin in the diets. For Exp. 5, two systems of four 4-L digestion vessels (Daisyll system, Ankom technology, NY, USA) were used in two consecutive runs of 48 h. The treatments were: orchard hay (0.4 g/bag), corn (0.4 g/bag), orchard hay (0.4 g/bag) + glycerin (0.2 g/bag) and corn (0.4 g/bag) + glycerin (0.2 g/bag). Orchard hay with glycerin inclusion presented lowest (P < 0.01) in vitro dry matter digestibility followed by orchard hay without glycerin, and corn treatments. There was a lack of effects for in vitro dry matter digestibility (P > 0.05) between corn with or without glycerin. We concluded that, under these experimental conditions, glycerin contributed more to the enhancement of methanogenesis than carbohydrates, but effectively replaced dietary corn as energy source at up to 30og/kg of the diet.